The influence of achievement motivation on the educational practice ability of pre-service teachers: the multiple mediating role of professional identity and learning engagement - Peng, Yanhong; Zhang, Cai (Frontiers in Psychology, 2024)
Objective According to Bronfenbrenner’s bioecological model of human development, focus on exploring the mechanism of person characteristics (achievement motivation) in their own development (improvement of educational practice ability). Method A survey was conducted on 1,225 pre-service teachers in Anhui Province, China, using the Achievement Motivation Scale, Professional Identity Scale, Learning Engagement Scale, and Educational Practice Ability Scale. Results (1) Achievement motivation can significantly and positively predict pre-service teachers’ educational practice ability; (2) Achievement motivation can indirectly affect pre-service teachers’ educational practice ability through the mediating effects of professional identity and learning engagement; (3) Professional identity and learning engagement play a chain mediated role in the impact of achievement motivation on pre-service teachers’ educational practice ability.